Dinamika Hukum Islam dan Hak Asasi Manusia dalam Gender dan Hukuman Mati - Sholihah, Mida Mar`atus; Sukarni, Sukarni; Hanafiah, M.; Muhajir , Ahmad (Sharia Journal and Education Center Publishing, 2024)
Abstract The dynamic relationship between Islamic law and human rights (HR) has been a complex and protracted debate. These two concepts have a long history and are interrelated, although there are some differences in their interpretation and application. This paper aims to analyze this dynamic, with a focus on two main issues: gender and the death penalty. Conceptually, Islamic law has actually contained teachings on HR since its birth in the 6th century, long before the concept of HR in the West emerged in the 17th and 18th centuries. However, in its development, there has been a debate regarding the interpretation and implementation of Islamic law, particularly in the issues of gender and the death penalty. The biological anatomical differences between men and women have given birth to a set of cultural concepts called gender, which then sparked debate over their roles and status in society. In addition, the application of the death penalty in Islamic law also becomes a point of contention with the HR concept that upholds the right to life. This study is expected to provide a more comprehensive understanding of the dynamic relationship between Islamic law and HR, and to serve as a basis for efforts to harmonize and resolve conflicts between the two. Keywords: Dynamic; Islamic Law; Human Right Abstrak Dinamika hubungan antara hukum Islam dan hak asasi manusia (HAM) telah menjadi perdebatan yang kompleks dan berkepanjangan. Kedua konsep ini memiliki sejarah yang panjang dan saling terkait, meskipun terdapat beberapa perbedaan dalam interpretasi dan penerapannya. Tulisan ini bertujuan untuk menganalisis dinamika tersebut, dengan fokus pada dua isu utama: gender dan hukuman mati. Secara konseptual, hukum Islam sejatinya telah mengandung ajaran tentang HAM sejak kelahirannya pada abad ke-6, jauh sebelum konsep HAM di Barat muncul pada abad ke-17 dan 18. Namun, dalam perkembangannya, terdapat perdebatan terkait penafsiran dan implementasi hukum Islam, khususnya dalam isu gender dan hukuman mati. Perbedaan anatomi biologis antara laki-laki dan perempuan telah melahirkan seperangkat konsep budaya yang disebut gender, yang kemudian memicu perdebatan mengenai peran dan kedudukan mereka dalam masyarakat. Selain itu, penerapan hukuman mati dalam hukum Islam juga menjadi titik perdebatan dengan konsep HAM yang menjunjung tinggi hak hidup. Kajian ini diharapkan dapat memberikan pemahaman yang lebih komprehensif mengenai dinamika hubungan antara hukum Islam dan HAM, serta menjadi landasan bagi upaya harmonisasi dan resolusi konflik di antara keduanya. Kata Kunci: Dinamika; Hukum Islam, Hak Asasi Manusia